The Interrelations of Celebrityendorsement, Social Media Use, and Customer Engagement in Achieving Customer Purchase Decision - Naila Syalsabila; Nurul Hermina (Budapest International Research and Critics University, 2023)
This study investigates the effect of celebrity endorsement and social media use on customer engagement and consumer purchasing decisions. This research was conducted on consumers of culinary and fashion products of SMEs in West Java Province, with a total sample of 185 respondents. The data was collected using the survey method of distributing questionnaires to respondents. Furthermore, the data obtained were processed using PL S Software-Structural Equation Modeling. The research results show that: (1) the use of social media has a positive effect on the customer; (2) The role of celebrity endorsement has a positive effect on customer engagement; (3) Customer engagement has an impact on purchasing decisions; (4) Customer engagement mediates the relationship between social media use and consumer purchasing decisions, and (5) Customer engagement mediates the relationship between celebrity endorsement and consumer purchasing decisions.